2007
DOI: 10.1017/s1751731107727490
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carcass maturity on meat quality characteristics of beef semitendinosus muscle for chinese native yellow steers

Abstract: This work was designed to study the effects of carcass maturity on meat quality characteristics and intramuscular connective tissue of beef semitendinosus muscle from Chinese native Yellow steers. Chemical determinations, histological and mechanical measurements were performed on the raw and cooked meat at 4 days post mortem. In raw meat, intramuscular fat, collagen solubility, mechanical strength and transition temperature of intramuscular connective tissue increased (P , 0.05) with carcass maturity before bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Meat quality and meat composition are not separated from the influences of animal genetic improvement systems. Previous studies have indicated that meat quality is tightly correlated with muscle composition and structure and the histological properties of muscle fibers [ 1 , 2 ]. It is therefore crucial to further study the molecular genetic mechanism of skeletal muscle growth and development [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meat quality and meat composition are not separated from the influences of animal genetic improvement systems. Previous studies have indicated that meat quality is tightly correlated with muscle composition and structure and the histological properties of muscle fibers [ 1 , 2 ]. It is therefore crucial to further study the molecular genetic mechanism of skeletal muscle growth and development [ 3 ].…”
Section: Introductionmentioning
confidence: 99%